The body the uniform cannot stitch: Signs, silences, and pluralities in amazonian education (Revista Contexto & Educação, 2026)
This study analyzes the meanings attributed to school uniforms in a state in the southwestern Brazilian Amazon. Through qualitative and documentary analysis, a public school uniform is examined, highlighting visual and textual elements that naturalize bodies and silence local identities. The methodology articulates three movements: visual analysis of the artifact, critique of educational legislation, and a decolonial proposal for aesthetic reconfiguration. Grounded in theorists such as Foucault, Bourdieu, and Bakhtin, whose dialogical approach guided the analysis of findings, the study reveals that the uniform functions as a technology of control by reproducing symbolic violence, excluding Indigenous languages and Amazonian epistemologies. The results indicate that standardization, though justified by discourses of equality, reinforces exclusion by imposing aristocratic symbols. As an alternative, the study proposes replacing colonial mottos with Indigenous expressions, incorporating local graphic elements, and adopting colors inspired by biodiversity, thereby transforming the uniform into an instrument of cultural resistance. The conclusion asserts that the school uniform is far from neutral; it is a political document whose redesign can reconfigure the school as a plural space, where the student body ceases to be a mere support for power and becomes a territory for dialogue between ways of knowing.
Keywords: School uniform; Decoloniality; Symbolic violence; Hidden curriculum; Amazon